Statistical Assurance of Process Validation of Celecoxib Capsules - Tejal, Sharma (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTA new simple, rapid and reliable Ultraviolet (UV) Spectrophotometry method was developed and validated for the estimation of celecoxib in blend and capsule formulations. The method was based on simple UV estimation in cost effective manner for regular laboratory analysis. The instrument used was Perkin Elmer, UV Spectrophotometer (Lambda 25) and using 0.1 N HCl as solvent system. Samples were analyzed using UV Win Lab 5.2.0 software and matched quartz cells 1 cm and was monitored at 255 nm. Celecoxib was used as an internal standard. Linearity was obtained in the concentration of 2-20Âµg/ml for celecoxib. The validation parameters tested as per ICH guidelines prove the suitability of this method. Drug excipient interactions were not found. Statistical tools like one way analysis of variance (ANOVA) and Bonferroniâ€™s multiple comparison tests were applied on results of blend uniformity and content uniformity, done on process validation batches.